Development and Realisation of a Real-Time High Precision Positioning SSR-RTK Service for the North Sea Exclusive Economic Zone - Jahn, Cord-Hinrich; Westfeld, Patrick; Vahrenkamp, Bernd; Wübbena, Gerhard; Schmitz, Martin; Schumann, Robert; Wallat, Christoph (The International Hydrographic Review, 2022)
In a two-year research and development project, the prototype of a GNSS (Global Navigation Satellite System) based real-time service using a SSR-RTK (State Space Representation-Real Time Kinematic) approach was developed for the German exclusive economic zone in the North Sea. Because the survey area of the North Sea can only be represented with a heterogeneous distribution of GNSS Continuously Operating Reference Stations, the calculation algorithm and the modelling of the GNSS correction data are particularly important. Maritime measurements in the survey area have confirmed the basic functionality of the prototype through an almost 90% availability of the RTK status fix with initialisation times of less than two minutes. Sea and land measurements as well as a permanent monitoring station were used to demonstrate the quality targets.